Effect of Surfactant Concentration on the Entrapment Efficiency Niosomes Aqueous Extract of Cassava Leaves (Manihot esculenta Crantz) (Asian Journal of Pharmaceutics (AJP), 2019)
Context: Aqueous extract of cassava leaves (Manihot esculenta Crantz) has a high rutin content. Rutin hasbenefits as an antioxidant, anti-inflammatory, analgesic, and antidiabetic. The plant extract has low bioavailabilityand has a large molecular weight. Therefore, a carrier system like niosomes is required to allow aqueous leavesextract of cassava through to absorb in the body. Aims: The purpose of this study was to determine the effectof variation concentration of Span 40 that can trap aqueous extract of cassava leaves in niosomes optimally.Materials and Methods: Niosomes were done by thin-layer hydration method with concentration of Span 40which was varied into three formulas: Formula A (100 Î¼mol), Formula B (150 Î¼mol), and Formula C (200 Î¼mol).Statistical Analysis Used: The data analysis using SPSS analyzed by one-way ANOVA. Results: The rutincontained in cassava leaves of this research is 42.52%. Entrapment efficiency test used dialysis membrane methodand the result showed that the increased concentration of Span 40 is used; the entrapment efficiency is alsoincreasing. The result of SPSS test using one-way ANOVA of three formulas did not show significant difference(P > 0.05). Conclusions: Optimum concentration of Span 40 in trapping aqueous extract of cassava leaves isFormula A (100 Î¼mol) which was 95.9%.